Long-range transport of La Soufrière volcanic plume to the western North Pacific: Influence on atmospheric mercury and aerosol properties. (1st January 2022) - Ravindra Babu, Saginela; Nguyen, Ly Sy Phu; Sheu, Guey-Rong; Griffith, Stephen M.; Pani, Shantanu Kumar; Huang, Hsiang-Yu; Lin, Neng-Huei
Abstract: Volcanic eruptions are important natural sources of gases and aerosols to the environment. However, their impact on the global cycle of trace elements, including mercury (Hg), remains poorly understood. On 9 April 2021, La Soufrière volcano (13.33°N, 61.18°W) erupted in the Caribbean Sea. Ozone Monitoring Instrument (OMI) measurements of sulfur dioxide (SO2 ) tracked the transport of volcanic SO2 in the troposphere over long distances from the source, including to the western North Pacific ∼10 day after eruption. A spike in gaseous and particle-bound mercury concentrations along with a peak in aerosol back-scattering coefficient at Lulin Atmospheric Background Station (LABS, 23.47°N, 120.87°E; 2862 m AMSL) coincided with the volcanic plume transport on 19 April. The slope of gaseous elemental mercury vs. carbon monoxide concentrations during the event was 0.027, which is distinctly higher than for Southeast Asia biomass burning (slope = 0.005) and East Asia outflow (0.011) pollution sources. Arrival of the plume high above Taiwan was confirmed by significant changes in signature aerosol properties. Thus, with critical observational evidence, our study reported for the first time enhanced mercury levels ∼18000 km downwind from a volcano source, providing an important check on volcanic Hg emission strength. Graphical abstract: Image 1 Highlights: Long-range transport of La Soufrière volcano plume to western North Pacific. First time volcanic Hg reported ∼18000 km downwind of eruption. Significant changes in signature columnar aerosol optical properties were also observed.